Anti-access warfare : countering A2/AD strategies - Tangredi, Sam J. (Annapolis, Maryland : Naval Institute Press, 2013)
"This is the first book to examine the concept of anti-access and area denial warfare, providing a definitive introduction to both conceptual theories and historical examples of this strategy. Also referred to by the acronym "A2/AD," anti-access warfare has been identified in American strategic planning as the most likely strategy to be employed by the People's Republic of China or by the Islamic Republic of Iran in any future conflict with the United States. While previous studies of the subject have emphasized the effects on the joint force and, air forces in particular, this important new study advances the understanding of sea power by identifying the naval roots of the development of the anti-access concept. Rather than arguing against the reliance on maritime forces--presumably because they are no longer survivable--Tangredi maintains that history argues that maritime capabilities are key to countering anti-access operations. "--
Includes bibliographical references (pages 277-295) and index.
Keywords: Sea control; Access denial (Military science); Strategy -- Case studies; Unified operations (Military science) -- Case studies